Pregnancy outcome in diabetic patients at the University College Hospital, U.C.H, Ibadan. (2003)
Context: Diabetes mellitus is one of the common medical complications in pregnancy, which if not properly controlled, can lead to significant perinatal and maternal morbidity and mortality. Objective: To determine the incidence of diabetes mellitus in pregnancy in this centre, and to assess the effect of maternal glucose control on the obstetric performance as well as perinatal outcome of pregnant diabetics managed at the University Collage Hospital, Ibadan. Study Design: A review of the obstetric outcome for 49 diabetic women who delivered at the University College Hospital, U.C.H, Ibadan, Nigeria during a 10-year period (January, 1991 to December 2000) is presented. Results: The incidence rate of diabetes in pregnancy was 0.74 per 1000 deliveries per year. Most patients (89.8%) booked for antenatal care and delivery in this centre. Good control was achieved in 77.6% of patients and the mean birth weight was 3.37 1.52kg. There was no significant difference in the birth weight and fetal outcome if a patient had pre-existing or gestational diabetes. However, the outcome was significantly related to the level of control. With good control there was a better Apgar score at 5 minutes, which was prognostic for fetal outcome. The perinatal mortality rate was 98/1000 births and this was significantly associated with poor control when compared with good control (p < 0.05). There was no maternal death. Conclusion: Further improvement in the management is needed. Preconception control, early antenatal booking and good control in pregnancy are strongly advocated as means of achieving good pregnancy outcome.